KOMPETENSI MANAJERIAL KEPALA MADRASAH DALAM KINERJA TENAGA KEPENDIDIKAN DI MADRASAH - Riska Aristianingsih; Irawan Irawan; Moh Sulhan (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
Based on the results of the 2012 madrasah principal competency test, it shows that the competence of madrasah principals in Indonesia is 70% out of 250 thousand with test scores below 75. This indicates that madrasah principals in Indonesia are incompetent or weak in the areas of managerial and supervisory competence. This research was conducted with the aim of knowing the relationship between the managerial competence of the madrasah principal and the performance of the education staff in Madrasah Negeri in Bandung Regency. This study used a quantitative approach, and distributed questionnaires to 59 education staff respondents in Madrasah Negeri in Bandung Regency with a sample consisting of the entire population. The researcher then used a Likert scale model as primary data which was distributed by coming directly to the madrasa and some others by going through the google form. The data analysis technique used is validity test, reliability test, partial analysis, normality test, linearity test, correlation test, regression test and coefficient of determination test. Based on the results of the analysis showed that there was a relationship between the managerial competence of the madrasah principal and the performance of the education staff in State Madrasahs in Bandung Regency. The results showed that the correlation coefficient value was 0.466, this value was included in the correlation category 0.40 – 0.59 (medium), while the significance value was 0.000 <0.05. Thus it can be concluded that H0 is rejected and Ha is accepted. This shows that there is a positive and significant relationship between managerial competence and the performance of education staff in State Madrasahs throughout Bandung Regency.